Fiber Optic Sensors and Applications VI 2009
DOI: 10.1117/12.817752
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of optical fibers in a cryogenic environment

Abstract: Optical fibers with various protective coatings were submerged in liquid nitrogen to 77°K then tested for mechanical and optical reliability. It was found that while all the fibers maintained strength after low-temperature exposure, the optical response varied depending on the protective coating. The optical attenuation observed for some fiber samples is due to axial shrinkage of the coating, which then leads to an elevated microbending loss. The behavior of the fiber coating at temperatures below the glass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In such configurations, the OPC and the input fiber can be directly immersed in liquid nitrogen or liquid argon. From our testing of different fiber types in immersed liquid nitrogen, we found that bare optical fibers with only a thin polyimide protective coating (no jacket) are preferred to minimize transmission losses in the fiber under cryogenic conditions [17]. It should be noted that bare polyimide-coated optical fibers are readily commercially available and have good mechanically integrity.…”
Section: Discussionmentioning
confidence: 93%
“…In such configurations, the OPC and the input fiber can be directly immersed in liquid nitrogen or liquid argon. From our testing of different fiber types in immersed liquid nitrogen, we found that bare optical fibers with only a thin polyimide protective coating (no jacket) are preferred to minimize transmission losses in the fiber under cryogenic conditions [17]. It should be noted that bare polyimide-coated optical fibers are readily commercially available and have good mechanically integrity.…”
Section: Discussionmentioning
confidence: 93%
“…The compression effects were expected to be caused by the jacket (the furcation tubing). Differences in the expansion coefficients of the dissimilar materials were expected to create micro-bends and additional light escape paths in the fiber [30].…”
Section: Resultsmentioning
confidence: 99%
“…For other applications, cryogenic temperature capabilities with minimal parasitic light leakage can be the main objectives, while still maintaining full galvanic isolation. This is the case for liquid argon or liquid xenon high-voltage time-projection chambers for fundamental neutrino detection and dark matter studies, or for cosmic muon research [24][25][26][27][28][29][30]. For applications requiring kilometers of optical power transmission, it is advantageous to develop PoF systems based on economically viable solutions, for example, using standard single-mode fiber (SMF) or multi-mode (MM) fiber cables.…”
Section: Introductionmentioning
confidence: 99%
“…As anticipated, fibers coated by polypropylene provide substantially worse strain transfer response at around 88%; in general, traditionally-coated optical fibers do not provide satisfactory performance for strain measurement applications. However, polyimide coatings are mature and have been demonstrated both at very low temperatures and in high-strain bonding applications 17,18 , and the aforementioned processes for the bulk coating of bare silica fibers with metalized buffer layers substantially improve the mechanical properties of the fiber, especially with respect to tensile strength. While there are no existing commercial offerings of Bragg gratingetched fibers having a metalized buffer, the requisite manufacturing technology exists and could be readily deployed.…”
Section: B Mechanical Stability and Bondingmentioning
confidence: 99%